Peran Media Sosial dalam Transformasi Budaya Pandhalungan - Suyono, Suyono (representamen, 2020)
AbstractPandhalungan culture is increasingly popular in Jember regency. Various cultural attractions in the community degree in the region, often wrapped with the term Pandhalungan. In fact, Jember Regency, routinely held the approval of the Jember cultural art with the name Pandhalungan Night Show. Pandhalungan is a term to describe the culture of assimilation between Javanese and Madura. Tumbuh-kembangnya Budaya Pandhalungan, especially in Jember district, is not separated from the role of media. One of them is social media, especially Facebook--widely used as a medium of communication in the Pandhalungan culture. Research with this descriptive analytical method uses a qualitative approach, to uncover the data that supports the role of social media in transforming the Pandhalungan culture in Jember district. As a result, the assimilation of these two cultures form a community spread from the north coast of East Java to some of the south coast of East Java, starting Lumajang, Jember, and part of Banyuwangi, continues to grow into local tourism potential. Keywords: social media, cultural transformation, pandhalungan